Analisis Kelayakan Usaha Peternakan Ayam Ras Petelur Di Kecamatan Baradatu Kabupaten Way Kanan Provinsi Lampung - Tri Anwar Yulianto; Novi Eka Wati; Riko Herdiansah (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
Abstract Laying hens have a very important role in providing animal protein needs in the community, as the population increases, egg consumption will also increase. So that laying hens have the potential to be developed, based on the economic aspect, researchers are interested in conducting research with the aim of analyzing the feasibility of laying hens in Baradatu District, Way Kanan Regency, Lampung Province. The research was conducted in Baradatu District, Way Kanan Regency, Lampung Province. The method to determine the research location is purposive sampling. Primary data was obtained through direct observation and interviews with farmers with a population of 2000, 5000, 15000. The data analysis in this study were production costs, revenues, income and R/C Ratio analysis. Based on the results of the study, it was concluded that laying hens with a population of 2,000, 5,000 and 15,000 from an economic point of view was feasible, because it had an R/C ratio > 1, namely 1.08, 1.11 and 1.19, respectively. The monthly income of laying hens with a population of 2,000 is Rp. 5,884,590,- population of 5,000 is Rp. 18,941,272,- and a population of 15,000 is Rp. 89,585,191,- This shows that the increasing population of livestock, the more feasible the chicken farming business. layer, because the value of the R/C ratio and income is also increasing. Keywords: Laying hens, Business Feasibility, Eggs.